The making of Christian Moravia (858-882) : Papal power and political reality - Betti, Maddalena, 1979- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2014)
In The Making of Christian Moravia Maddalena Betti examines the creation of the Moravian archdiocese, of which St Methodius was the first incumbent, in the context of ninth-century papal policy in central and south-eastern Europe. In the nineteenth and twentieth century religious and nationalistic concerns widely influenced the reconstruction of the history of the archdiocese of Methodius. Offering a new reading of already widely-used sources, both Slavonic and Latin, Maddalena Betti turns attention upon the jurisdictional conflict between Rome, the Bavarian churches and Byzantium, in order to uncover the strategies and the languages adopted by the Apostolic See to gain jurisdiction over the new territories in central and south-eastern Europe.